Assessment of Nursing Students' Knowledge about The Random Use of Antibiotics at College of Nursing in Al-Qadisiyah University - Dakhil, Shaima Hasan; Ibtisam Rahman Jasim; Estabraq Ahmed Chyadh (Indonesian Journal on Health Science and Medicine, 2025)
Antibiotics are either made from microorganisms or created in a lab. They work by killing or slowing down the growth of living organisms. to assess knowledge about the random use of antibiotics among nursing students at nursing College in Al- Al-Qadisiyah University. A quantitative Research was conducted to evaluate understanding and awareness regarding the random use of antibiotics. Between January 13, 2021, and May 20, 2021, both study and control groups were formed. A random sample of 170 participants, consisting of both males and females, was chosen. using Antibiotics among nursing students at nursing College in Al- Qadisiyah university . Data were collected during period (13th of January to 6 July) Using interview Technique. Data analyzed by using spss Ver23. The result of study showed that highest proportion Of the participants in the study, 51% were aged between 18 and 20. Among them, 85% were female and 15% were male. Additionally, 83% resided in urban areas, while 87.64% had a good understanding of the random use of antibiotics. A Useful assertion found in this study was that most of students practiced reading drug labels for composition and expiry dates. Most common source of information was pharmacology It was found that second-stage nursing students and read the prescription provided with the medicine carefully. Although antibiotics are generally considered safe, they have been associated with There are many different negative effects, and the side effects can be many and diverse. Highlights: Most nursing students (87.6%) demonstrated good knowledge regarding the random use of antibiotics. Significant associations were found between students’ knowledge and demographic factors such as residence and age. Pharmacology courses and reading drug labels were the main sources of antibiotic knowledge among students.